HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN PERILAKU MENYONTEK PADA MAHASISWA UST - Maria Novita Reyaan; TA. Prapancha Hary (JURNAL SPIRITS, 2015)
ABSTRACT            The purpose of this study is to determine of the Relationship Self Confidence with Behavior Cheating of college student in University Sarjanawiyata Tamansiswa and to know the significant of Self Confidence function to percepsion of behavior cheating.             Subjects in this study were between 18 – 24 years old college student of the University Sarjanawiyata Tamansiswa. Sampling technique was cluster random sampling . The method of analysis used in this study is the Product Moment Correlation.             Result of data analysis variable Self Confidance with variable Behavior Cheating the value r -0,681 with p = 0.000 ( p < 0,05 ). Based on the results of the correlation can be stated that there is a significant negative relationship between Self Confidence by Behavior Cheating college student Universitas Sarjanawiyata Tamansiswa. Correlation test results showed that the variable Self Confidence with Behavior Cheating of college student has determinant coefficient of 46%. It shows that 54% that Behavior Cheating of college student is fixed by other factors that give influence.  Keywords: Self Confidence, Behavior Cheating